Art outcome in combined group of women with premature ovarian failure and menopausal women - Rajendrakumar, Rekha; Nadkarni, Purnima K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: It is to present an overview of the study of the ART cycles in combined group of women with premature ovarian failure (POF) and menopausal women in 1 year period. Purpose of the study was to know the pregnancy outcome in this combined group. Since majority of the patients who entered our tertiary hospital had already received various treatment methods such as gonadotropins, long protocols and ultra-short protocols in previous hospitals with no positive result, we had to take them directly to the ovum donation (OD) or embryo donation (ED). Methods: A simple study was performed from 1st January, 2015 to 31st December, 2015. Women with POF and menopause were enrolled and complete follow up of them was done from their first visit till stable pregnancy of 14 weeks was achieved. While doing this, we considered various parameters which can affect the ART outcome, for e.g. endometrial evaluation, hysteroscopy findings, proliferative phase preparation, leuteal support, semen analysis etc. The study outcome results included pregnancy rate and miscarriage rate. Results: In spite of good efforts, ultimately, stable pregnancy rate (beyond 14 weeks gestation) of these women was only 35% that was almost one third of the total study population that too with the help of OD and ED. Pregnancy rate was actually 42%, out of which 7% had miscarriage. With all the cost, efforts and time involved, 65% (2/3rd) of women could not achieve successful pregnancy. Conclusions: Since the possibility of pregnancy gradually declines after the age of 30 and a steep fall in fertility after the age of 35, women should be advised not to postpone marriages and should be encouraged to have children earlier.